Semisynthetic Vitamin E Derivatives as Potent Antibacterial Agents against Resistant Gram‐Positive Pathogens. (8th December 2020) - Viault, Guillaume; Kempf, Marie; Ville, Alexia; Alsabil, Khaled; Perrot, Rodolphe; Richomme, Pascal; Hélesbeux, Jean‐Jacques; Séraphin, Denis
Abstract: New 5‐substituted vitamin E derivatives were semisynthesized, and their antibacterial activity against human Gram‐positive and Gram‐negative pathogens was evaluated. Several vitamin E analogues were active against methicillin‐resistant Staphylococcus aureus (MRSA) and/or methicillin‐resistant Staphylococcus epidermidis (MRSE); structure‐activity relationships (SARs) are discussed. As a result, it is shown that the presence of a carboxylic acid function at the C‐5 position and/or at the end of the side chain is crucial for the antibacterial activity. The bactericidal or bacteriostatic action of three compounds against MRSA and MRSE was confirmed in a time‐kill kinetics study, and the cytotoxicity on human cells was evaluated. The preliminary mechanism study by confocal microscopy indicated that those vitamin E analogues led to bacterial cell death through membrane disruption. Abstract : Vitamin E derivatives were semisynthesized and antibacterial activity of 28 compounds was evaluated against pathogens. Cytotoxicity and time‐kill curves of the most active molecules were realized and confocal microscopy study indicated that 3 j kills bacteria through the disruption of cell membrane.